Complete mitochondrial genome of Dahlica (Dahlica) ochrostigma Roh and Byun, 2018 (Lepidoptera: Psychidae) - Seung Jin Roh; Da-Som Kim; Bong-Woo Lee; Bong-Kyu Byun (Mitochondrial DNA. Part B. Resources, 2019)
We, herein, report the complete mitochondrial genome of Dahlica (Dahlica) ochrostigma. This species’ genome has a total length of 15,429 bp (GenBank accession number: MK890245), consisting of 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and an A + T rich control region. The nucleotide composition is 39.1% T, 42.8% A, 11.1% C, and 7.0% G. This is the first report of a complete mitochondrial genome of the subfamily Naryciinae, and this mitogenomic sequence can be used as a reference for phylogenetic studies on the family Psychidae.